Pelaksanaan Rencana Kegiatan Tahunan yang Mengatur CSR Pada BPR di Kabupaten Badung - I Made Arjaya; Desak Gede Dwi Arini; P. B. Pramana (Kertha Wicaksana, 2020)
This study focuses on the application of Corporate Social Responsibility (referred in CSR) in Bank Perkreditan Rakyat (BPR), in Badung Regency. This BPR is expected to be able to prosper the surrounding community and carry out the mandate of PERDA Badung Regency No. 6 of 2013 concerning Corporate Social Responsibility. This research has two problem formulations, namely how is the arrangement of CSR in the BPR annual activity plan in Badung Regency and how is the implementation of the annual activity plan governing CSR in the BPR in Badung Regency. The method used is the empirical research method. This research is directly looking for data to the field. The results of the study show that corporate social responsibility is a company's commitment in improving the community's economy which is beneficial to the company and the general public. The regulation of corporate social responsibility at BPRs in Badung Regency, namely Law No. 40/2007 concerning Limited Liability Companies, PP No. 47/2012, and Badung Regency Regulation No. 6/2013. In the implementation of CSR in BPR in Badung Regency, it has been running well as in terms of education, scholarships for outstanding students and introduction of banking products to the local community.